Masyarakat Sipil, Modal Sosial dan Tata Pemerintahan Yang Demokratis - - Suharko (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2005)
Discourse and promotion of democratic governance in developing countries has been part of agendas and interests of international donor agencies. This article shows that donor agencies closely refer to the Neo-Tocquevillian school in promoting democratic governance in developing countries that entering political transition towards democracy. This school argues that civil society organizations (CSOs) have potentials dan capability in developing democratic governance through building social capital. In the line of this argument and mapping out of the diversity of CSOs, this article argues that although Indonesian CSOs face some serius problems, to some extent, they contributed in promoting democratic governance.